Traumatic spinal cord injury caused by suspected hyperflexion of the atlantoaxial joint in a 10-year-old cat. Issue 1 (9th June 2015) - Wessmann, Annette; McLaughlin, Angela; Hammond, Gawain
Case summary: A 10-year-old cat presented 5 days after a traumatic event with acute recumbency followed by some clinical improvement. The neuroanatomical localisation was the C1–C5 spinal cord segments. Initial survey radiographs, including lateral flexed views, showed no convincing abnormalities. Magnetic resonance imaging (MRI) revealed a marked focal intramedullary lesion at the level of the dens and suspected oedema extending over C2–C3 vertebrae, suggesting early syrinx formation. The cat made an initial excellent recovery on restricted exercise without medical treatment. The MRI changes largely resolved on follow-up MRI 4 weeks later yet recurred following a relapse 4 months later. At this stage, a post-traumatic syrinx had developed. Moreover, the suspected atlantoaxial instability was finally diagnosed on radiography with fully flexed lateral views. A hyperflexion injury causing tearing of the atlantoaxial ligaments was considered most likely given the lack of malformations or fractures. The cat made a full recovery on conservative management. Relevance and novel information: This is the first report of sequential MRI findings in a cat with atlantoaxial instability. Moreover, post-traumatic syringomyelia formation following atlantoaxial injury has not been reported. Sequential MRI aids in the diagnosis of hyperflexion injury if survey radiographs fail to identify atlantoaxial instability.